Symport and antiport mechanisms of human glutamate transporters - Biao Qiu; Olga Boudker (Nature Communications, 2023)
Abstract Excitatory amino acid transporters (EAATs) uptake glutamate into glial cells and neurons. EAATs achieve million-fold transmitter gradients by symporting it with three sodium ions and a proton, and countertransporting a potassium ion via an elevator mechanism. Despite the availability of structures, the symport and antiport mechanisms still need to be clarified. We report high-resolution cryo-EM structures of human EAAT3 bound to the neurotransmitter glutamate with symported ions, potassium ions, sodium ions alone, or without ligands. We show that an evolutionarily conserved occluded translocation intermediate has a dramatically higher affinity for the neurotransmitter and the countertransported potassium ion than outward- or inward-facing transporters and plays a crucial role in ion coupling. We propose a comprehensive ion coupling mechanism involving a choreographed interplay between bound solutes, conformations of conserved amino acid motifs, and movements of the gating hairpin and the substrate-binding domain.